China's Changing Consumer Market and the Policy Implications - Jinkook Lee (Korea Development Institute (KDI), 2016)
China's rural consumer market has exhibited extraordinary growth. Over the past decade, the consumption growth rate and average propensity to consume of rural residents have surpassed those of their urban counterparts, with the former's consumption patterns becoming increasingly similar to the latter's. Such a phenomenon prevails in rural areas that neighbor 2nd and 3rd tier cities whose urbanization is progressing rapidly. Accordingly, Korean companies must diversify their products in line with China's expanding rural markets while further differentiating product composition to satisfy the heterogeneous demands in urban markets. As for the government, efforts must be placed in strengthening the export cooperative system targeting China between domestic manufacturers, distributors (operating in China) and logistics companies. - This study aims to analyze the growth of and changes in China's consumer market to gain a better understanding and to discuss the future direction of governmental and corporate responses - China's consumer market started to grow in full swing in the mid-1990s and exhibited continued explosive growth since the mid-2000s. - China's consumer market grew to the world's second largest in 2013 with a market scale of 3.4 trillion. - Over the past three decades, the nominal consumption expenditure of urban and rural residents has expanded over 20 fold. - Overall, the consumption growth of rural residents have surpassed that of urban residents since 2004. - The APC of rural residents exceeded that of urban residents in 2005. - When limited to cashonly consumption, rural residents' APC has improved continuously. - Consumption growth rate by item is found to be higher in rural residents than in urban residents. - China's rural areas today are also experiencing servitization in line with the increases in income and consumption. - Consumer markets in the 2nd and 3rd tiers have spurred the consumption growth in rural areas. - Urban areas are showing slower growth due to the reduced consumption by residents in 1st tier cities. - Consumption growth in urban 2nd and 3rd tiers has been steadily maintained at a relatively high 11%. - Urbanization rate has risen fast mainly in prefecture-level cities in 2nd and 3rd tiers, and there is enough room for additional increase. - A 1%p rise in the urbanization rate equals an increase of 93 yuan in the annual average per capita consumption and 123.6 billion yuan in China's total consumption. - Urbanization which results in the rise in consumption goes beyond urban areas to reach neighboring rural areas. - The contribution of urbanization to the rise in consumption is confirmed in all estimated results. - Domestic consumer goods manufactures need to be actively encouraged to enter China's rural markets with diverse products. - Product composition targeting urban consumer markets must be differentiated, relying on the collaboration between Korean distributors in China and domestic consumer goods manufacturers. - The Korean government should strengthen the cooperative export system targeting China between Korean distribution companies operating in China and domestic consumer goods companies as well as the logistics companies that link them.
Keywords: 330